The social conflict for the administration of the municipal aqueduct in Heredia (1973-1975) - Montero Hernandez, Diego (2023)
Introduction. This article provides inputs in the generation of knowledge about conflicts on natural resources in Costa Rica, continuing the field of research that has addressed the complex relationship between Costa Rican citizens and its Welfare State in the second half of the 20th century.Objective. To identify the main social and political events that were generated in the province of Heredia as a result of the administration of the aqueduct between Heredia Municipal Council and National Service of Aqueducts and Sewers in the mid-1970s.Method. It was used a qualitative methodology based on the analysis of primary sources, such as newspapers and Heredia Municipal Council´s minutes, between 1973 and 1975.Results. Between 1973 and 1975 one of the decade’s fiercest conflicts against the National Service of Aqueducts and Sewers occurred in Heredia, as a result of some causes: infrastructural (poor physical conditions in the aqueduct distribution network), administrative (technical inability of the Municipality to guarantee drinking water service), and political-social (opening of political opportunities within a cycle of protest against the SNAA and development of a framework for collective action).Conclusions. This case study shows local resistances samples in the struggle for natural resources control among various social actors and public institutions, such as National Service of Aqueducts and Sewers, in the midst of boom years of the Costa Rican Welfare State.